2013
DOI: 10.1071/en13016
|View full text |Cite
|
Sign up to set email alerts
|

Role of sea salt aerosols in the formation of aromatic secondary organic aerosol: yields and hygroscopic properties

Abstract: Environmental context In the coastal and ocean environment, oil spills and ship movement can produce hazardous, organic aerosols. In this study, the role of sea salt in the formation processes of crude-oil-derived organic aerosols derived was explored, and it was found that sea salt can greatly increase the formation and growth of these toxic aerosols. Understanding of this process is crucial for evaluating the effect of oil spills and ship movements on air quality and human health. Abstract Dual, large (52m3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Organic aerosols in forest regions typically consist of a significant amount of biogenic SOA, formed from the photo-oxidation of the biogenic volatile organic compounds and condensation of low-and semi-volatile oxidation products. Preexisting sea salt particles could act as seeds for SOA formation (Beardsley et al 2013). It was not surprising that a considerable amount of OC was associated with sea salt aerosols.…”
Section: Contributions Of Fungi To Coarse Carbonaceous and Potassium mentioning
confidence: 99%
“…Organic aerosols in forest regions typically consist of a significant amount of biogenic SOA, formed from the photo-oxidation of the biogenic volatile organic compounds and condensation of low-and semi-volatile oxidation products. Preexisting sea salt particles could act as seeds for SOA formation (Beardsley et al 2013). It was not surprising that a considerable amount of OC was associated with sea salt aerosols.…”
Section: Contributions Of Fungi To Coarse Carbonaceous and Potassium mentioning
confidence: 99%
“…ATD contains hygroscopic inorganic salts that form the thin water film on the surface of ATD particles when the salts are deliquescent (or above ERH). Some salts such as magnesium sulfate and calcium sulfate can be hydrated even at low humidity (Beardsley et al, 2013;Jang et al, 2010). Gustafsson et al (2005) reported that ATD particles showed a substantially high affinity to water compared to pure CaCO 3 particles.…”
Section: Gas-dust Particle Partitioningmentioning
confidence: 99%
“…Moreover, the further reactive uptake of N 2 O 5 was reported to be dependent on the chloride to nitrate ratio of the reacted SSAs and their phases . The primary and secondary organics, biogenic particulates, sea-salt sulfates (ss-SO 2− 4 ), non-sea-salt sulfates (nss-SO 2− 4 ), etc., add greater complexity to these SSAs (O'Dowd and de Leeuw, 2007;Keene et al, 2007;Prather et al, 2013;Beardsley et al, 2013;Ault et al, 2013b). A detailed knowledge of the hygroscopic properties, mixing states, and the spatial distribution of the chemical components in NaClNaNO 3 mixture particles, as partially or fully reacted SSA surrogates, can serve as a good preliminary step to a better understanding of the complex chemical/physical mixing states, hygroscopic behavior, and reactivity of ambient SSAs.…”
Section: Gupta Et Al: Hygroscopic Properties Of Nacl and Nano 3 Mmentioning
confidence: 99%
“…Although real ambient SSAs are complex mixtures containing NaCl, other inorganic salts, and organics (O'Dowd and de Leeuw, 2007;Keene et al, 2007;Prather et al, 2013;Beardsley et al, 2013;Ault et al, 2013b), NaCl particles have been studied as genuine SSA surrogates in many laboratories (Martin, 2000;Krieger et al, 2012). Based on the experimental phase diagrams of deliquescence and efflorescence for the NaCl-NaNO 3 system (Figs.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%